The EGF receptor is an actin-binding protein (The Rockefeller University Press, 1992)
In a number of recent studies it has been shown that in vivo part of the EGF receptor (EGFR) population is associated to the actin filament system. In this paper we demonstrate that the purified EGFR can be cosedimented with purified filamentous actin (F-actin) indicating a direct association between EGFR and actin. A truncated EGFR, previously shown not to be associated to the cytoskeleton, was used as a control and this receptor did not cosediment with actin filaments. Determination of the actin-binding domain of the EGFR was done by measuring competition of either a polyclonal antibody or synthetic peptides on EGFR cosedimentation with F-actin. A synthetic peptide was made homologous to amino acid residues 984-996 (HL-33) of the EGFR which shows high homology with the actin-binding domain of Acanthamoeba profilin. A polyclonal antibody raised against HL-33 was found to prevent cosedimentation of EGFR with F-actin. This peptide HL-33 was shown to bind directly to actin in contrast with a synthetic peptide homologous to residues 1001-1013 (HL-34). During cosedimentation, HL-33 competed for actin binding of the EGFR and HL-34 did not, indicating that the EGFR contains one actin-binding site. These results demonstrate that the EGFR is an actin-binding protein which binds to actin via a domain containing amino acids residues 984-996.